COMPARATIVE STUDY OF PULSED MICROWAVE AND HYDRODISTILLATION EXTRACTION OF PIPERINE OIL FROM BLACK PEPPER - OLUSEGUN ABAYOMI OLALERE (International Islamic University Malaysia Engineering Journal, 2017)
Black pepper is a tropical crop with an extensive medicinal potential in alternative medicine and nutraceutical applications. The pungent bioactive piperine is responsible for this functions and its efficacy requires an efficient extraction technologies for optimal isolation. There is therefore a need to determine the best factor settings that will optimize the relative efficiency of the extraction system with minimal variability. The best factor settings was achieved using the L9 Taguchi parametric orthogonal design. The extraction parameters considered under this study were extraction time, irradiation power level, particle size and molar ratio. An optimal extraction condition was therefore achieved at 90 min extraction time, 350 W microwave power, 0.105 mm particle size and 10 mL/g molar ratio. The signal-to-noise ratio (SNR) otherwise known as response optimizer is an ideal metric in the determination of this optimum condition. The performance evaluation of reflux microwave extractor in relation to that of the hydrodistillation system placed the optimal efficiency and signal-to-noise ratio at 155.72% and 43.8469, respectively. The higher optimal efficiency obtained indicated that the microwave reflux extraction is better and more efficient than the conventional hydrodistillation techniques.